Technology development mode of communication/sensing/computing/intelligence integration - Xiangyang DUAN; Li YANG; Shuqiang XIA; Zhiqiang HAN; Feng XIE (Dianxin kexue)
Various new functions and services related to communication/sensing/computing/intelligence have been targeted, developed and fused into the existing 5G-Advanced and emerging 6G new system.The technical scenarios and use cases of communication/sensing/computing/intelligence integration and its expectation for technique mode requirementin 5G-Advanced and 6G different phases were addressed, meanwhile five characteristics of its technology development mode were extracted.The proposed viewpoints may guide the research and development of 5G-Advanced system and standardization process of 6G new system in future, leading to more effective and profitable applications and maximization of business value from communication/sensing/computing/intelligence integration.